Peran Kepala Sekolah dalam Pengembangan Karakter Siswa Berbasis Profesionalisme Guru - Ahmad Mushthofa; Muhammad Amin Khizbullah; Reza Aditya Ramadhani (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2022)
Abstract Education is not only focused on the intellectual factors that a person has while studying but also must be integrated with other factors such as attitudes, behavior, and character. With this, the article describes the role of the principal at SMK Cendekia Madiun in developing professional teachers in the educational process who can improve student character. The data collection technique used is interviews. Data processing and analysis techniques through data reduction, data presentation, and drawing conclusions. The role of school principals in improving teacher professionalism at Cendekia Vocational Schools by empowering teachers is manifested in IHT (in House Training) activities, KKG (Teacher Working Group) or MGMP (Subject Teacher Consultations) activities and directing teachers to set good examples, provide guidance, direction, holding character development, extra-curricular and religious activities. As well as creating new activities in the form of planting vegetables and raising catfish which are divided into each class. In addition, SMK Cendekia Madiun holds character development activities that instill the character of students who are honest, disciplined, independent, creative, love the homeland, democratic attitude, hard work, love to read, care for the environment, social care, religious, sense of responsibility, and especially according to the school's vision and mission that can develop students who are skilled, competitive, have faith and fear God Almighty. Keywords: Principal, Student Character, Teacher Professionalism